Immersion time of gutta percha points in various concentrations of zephiran chloride - Fran, Grace Marie; Pambid, Lourdes; Manuel, Loida S. (Adviser).
The optimum immersion time of gutta percha points in various concentrations of zephiran chloride as a disinfecting solution was investigated for the maintenance of the chain of asepsis during obturation of the root canal.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Gutta percha; Zephiran Chloride; Dental materials; Root canal filling materials